The Impact of Implementing Game-Based Learning on Student Motivation and Engagement - Agustina, Ika; Joshua, Wang; Julanos, Julanos; Niva, Matteson (Journal Emerging Technologies in Education, 2024)
Background:The implementation of game-based learning is an inclusive learninggame elements into an educational context. These game elements will produce a more dynamic and interesting learning experience. This interesting interactive experience encourages students to become more involved, thereby fostering a strong desire to understand and master the learning material. Research purposes:This research was conducted with the aim of understanding the relationship between the implementation of game-based learning and student motivation and engagement. Apart from that, it also aims to find out the challenges of implementing game-based learning. Method:The method used in this research is a quantitative method.This method is a way of collecting numerical data that can be tested. Data was collected through distributing questionnaires addressed to students. Furthermore, the data that has been collected from the results of distributing the questionnaire will be accessible in Excel format which can then be processed using SPSS. Results:From the research results, it can be seen that game-based learning is something that has become a trend in the world of education.By adapting technology to game-based learning, education can become more relevant and dynamic, and students' diverse learning styles can be accepted. Conclusion:From this research, researchers can conclude that the impact of implementing game-based learning,can encourage students to participate more actively in the learning process. So that student motivation and involvement becomes higher in the learning process.